From Implementation to Design: Tailoring and the Emergence of Systematization in CSCW - Trigg, Randall H.; Bødker, Susanne (DAIMI Report Series, 1994)
In this paper, we look at how people working in a governmental labor inspection agency tailor their shared PC environment. Starting with standard off-the-shelf software, the tailors adapt that software to the particular workplace in which they are embedded, at the same time that they modify and extend the practices of that workplace. Over time, their adaptations and the tailoring processes themselves become structured and systematized within the organization. This tendency toward systematization is in part a response to the requirement that the results of tailoring be sharable across groups of users. Our study focuses on several dimensions of the work of tailoring: construction, organizational change, learning, and politics. We draw two kinds of lessons for system development: how better to support the work of tailors, and how system developers can learn from and cooperate with tailors.